2017
DOI: 10.3390/en10111695
|View full text |Cite
|
Sign up to set email alerts
|

Combustion Characteristics of Single Particles from Bituminous Coal and Pine Sawdust in O2/N2, O2/CO2, and O2/H2O Atmospheres

Abstract: Burning fuels in an O 2 /H 2 O atmosphere is regarded as the next generation of oxy-fuel combustion for CO 2 capture and storage (CCS). By combining oxy-fuel combustion and biomass utilization technology, CO 2 emissions could be further reduced. Therefore, this work focuses on investigating the combustion characteristics of single particles from bituminous coal (BC) and pine sawdust (PS) in O 2 /N 2 , O 2 /CO 2 and O 2 /H 2 O atmospheres at different O 2 mole fractions (21%, 30%, and 40%). The experiments were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…It was also concluded that the ignition delay time dwindled as the oxygen concentration rose. Lei et al also obtained a similar phenomenon in the single‐particle combustion experiment of bituminous coal and pine sawdust in the DTF. Moreover, when the oxygen concentration increased between 50% and 100%, oxygen had less influence on ignition delay time than low oxygen concentration.…”
Section: Resultsmentioning
confidence: 57%
“…It was also concluded that the ignition delay time dwindled as the oxygen concentration rose. Lei et al also obtained a similar phenomenon in the single‐particle combustion experiment of bituminous coal and pine sawdust in the DTF. Moreover, when the oxygen concentration increased between 50% and 100%, oxygen had less influence on ignition delay time than low oxygen concentration.…”
Section: Resultsmentioning
confidence: 57%
“…Oxy-fuel (O 2 /CO 2 ) combustion was proposed as a retrofit technology to allow for the capture and storage of CO 2 in new or existing air-fired coal boilers [18][19][20]. Recently, it reached a milestone 35 MW load [21].…”
Section: Introductionmentioning
confidence: 99%
“…The processes of heating, ignition, and combustion are recorded using a video camera. This approach is considered practical and convenient and is often used for studying the combustion behavior of fuels in different conditions [28]. It should be noted that different holders can lead to changes in the heat transfer conditions in a CLF droplet suspended on them, for example, they can increase the heat sink to the holder from the droplet surface or an additional heat flux through the holder to the fuel.…”
Section: Heating Of a Fuel Particle On The Holder In The Flow Of Heatmentioning
confidence: 99%